Biomaterials-Based Antioxidant Strategies for the Treatment of Oxidative Stress Diseases - Maria Perez-Araluce; Tomasz Jüngst; Carmen Sanmartin; Felipe Prosper; Daniel Plano; Manuel M. Mazo (Biomimetics, 2024)
Oxidative stress is characterized by an increase in reactive oxygen species or a decrease in antioxidants in the body. This imbalance leads to detrimental effects, including inflammation and multiple chronic diseases, ranging from impaired wound healing to highly impacting pathologies in the neural and cardiovascular systems, or the bone, amongst others. However, supplying compounds with antioxidant activity is hampered by their low bioavailability. The development of biomaterials with antioxidant capacity is poised to overcome this roadblock. Moreover, in the treatment of chronic inflammation, material-based strategies would allow the controlled and targeted release of antioxidants into the affected tissue. In this review, we revise the main causes and effects of oxidative stress, and survey antioxidant biomaterials used for the treatment of chronic wounds, neurodegenerative diseases, cardiovascular diseases (focusing on cardiac infarction, myocardial ischemia-reperfusion injury and atherosclerosis) and osteoporosis. We anticipate that these developments will lead to the emergence of new technologies for tissue engineering, control of oxidative stress and prevention of diseases associated with oxidative stress.